(3LQjeI GdEQgGH aj VhA bGfhf GdcjGfGJ GdEQgGHjI Qbe (B8 (3dSfI (B2015 /s - (3eUWai Ydj YHO GdefYe GdYbHjs; (3oYeQ eMeO eMeO SGdes; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI(B:s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2023)
(3CVMJ XGgQI GdEQgGH gj CNWQ GdLQGFe GdJj Jdbj HXdGdgG Ydi LejY Ohd GdYGde, aJYOOJ CSGdjH hCOhGJ GdLeGYGJ GdEQgGHnqjI, hJfhYJ eUGOQ JehjdgG, hfJjLI ddJWhQ GdJcfhdhLj GdQgjH, CUHMJ fJGFL gPG GdfhY ef GdLQGFe eOeQI dcjGfGJ GdOhd, hJeJO ddaQO hGdeLJeY Ohf GdJejjR Hjf aFI hCNQi, hJgOa GdLeGYGJ GdEQgGHnqjI ef hQGA Pdc Edi JMbjb CZQGVgG GdELQGenqjI GdeJeKdI aj ELHGQ cjGfGJ GdOhd Ydi GdbjGe HYed Ch GdGeJfGY Yf Yed(B. (3hCeGe gPg GdNWhQI GdELQGenqjI ddJfXjeGJ GdEQgGHnqjI hYfGUQgG GdELQGenqjI, GJLgJ cGaI GdJTQjYGJ GdLfGFnqjI GdMOjKI Edi ehGLgI gPg GdXGgQI ehVhYkqjG hELQGFkjG, ehGLgI ef TCfgG JMLje gPg GdXGgQI hbWY eUGOQ JehjdgG hJbhjV MQcI YfGUQgG hGdefJejf dgG(B.(3hJYQVJ eUQ deNGWQ GdEQgGH, heMGhdGJ GdLeGYGJ GdEQgGHnqjI ddfjd ef CefgG hGSJbQGQgG hJgOjO CefgG Gdbhej, haj gPG GdEWGQ HGJ GdbVGA Ydi gPg GdJfXjeGJ gh Ld GgJeGe CLgRI GdCef GdeUQnqjI, hdeG cGfJ chGOQ gPg GdJfXjeGJ GdgGQHjf aj GdNGQL, JMGhd EUdGM GdYWH GdPj CUGH BdjJgG aj GdUeje hGNJQbJ JfXjeGJgG hJehjdGJgG fJjLI deG Mbbg LgGR GdCef GdeUQj ef fLGM eQehb, ef NdGd JNWjW eOQhS hacQ hGY hJfXje eMce hJWhQ LRQj dBdjGJ GdehGLgI GdCefnqjI, Laa YdjgG GdJehjd hbWY YdjgG GdJhLjg GdNGQLj GdeZQV(B. s
The phenomenon of terrorism has become the most dangerous crime that casts a shadow over all countries of the world. The methods and tools of terrorist groups have multiplied, and their sources of financing have diversified. As a result of the terrible technological development, the results of this type of crime have become devastating to state entities, and extend to the individual and society without distinguishing between one group or another. The groups aim Terrorist organizations seek to achieve their criminal goals of forcing state entities to take action or abstain from action. In the face of this criminal danger of terrorist organizations and their criminal elements, all modern criminal legislation has tended to confront this phenomenon objectively and procedurally, a confrontation that would curb this phenomenon, cut off its sources of funding, and undermine the movement of its members and affiliates. Egypt was exposed to the dangers of terrorism and the attempts of terrorist groups to undermine its security and stability and threaten its security. In this context, eliminating these organizations has become the main concern of the Egyptian security services, and since the cadres of these organizations fleeing abroad are trying to repair the damage that has struck their mechanism at the core and their organizations and finances have been penetrated as a result of the remarkable success achieved by the Egyptian security apparatus, through planning Thoughtful thinking, conscious thought, tight organization, and a radical development of security confrontation mechanisms have dried up funding and cut off malicious external guidance.
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI(B-(3cdjI GdMbhb(B-(3bSe GdbGfhf GdLfGFj, (B2023s
(3HHdjhLQGajG(B: (3UaMGJ (B531-565.s
(3GdfU HGdYQHjI hGdedNU HGdEfLdjRjI(B.s
Keywords: (3GdbGfhf GdLfGFjs; (3GdehGLgI GdCefjIs; (3GdLeGYGJ GdEQgGHjI s; (3GdGQgGHs; (3GdJTQjYGJ GdLfGFjI s; (3GdJWhQ GdJcfhdhLjs; (3eUGOQs; (3GdJfXjeGJs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs